Monitoring physical behavior in pediatric physical therapy: A mixed methods feasibility study to evaluate a newly developed toolkit and training - Barbara Engels; Elles Kotte; Raoul Engelbert; Marleen E. Sol; Remko van der Lugt; Harriët Wittink; Jan Willem Gorter; Manon A. T. Bloemen (PLoS ONE, 2025)
Introduction Pediatric physical therapists (PPTs) aim to enhance active physical behavior but lack feasible accelerometry devices to assess and evaluate physical activity (PA). We developed an activity monitoring prototype toolkit (AM-p Toolkit) consisting of a wearable, a docking station, a digital tool for data analysis, and physical tools for communication with children and parents. A training for PPTs was also created. We aim to explore the feasibility of the AM-p Toolkit from the perspectives of PPTs, children, and parents and to assess if training improved PPTs’ knowledge, skills, and confidence in using the Toolkit. Participants and methods Using an explanatory sequential mixed methods design, we collected data through questionnaires, individual interviews, and focus groups, guided by Bowen’s dimensions of ‘acceptability,’ ‘demand,’ and ‘practicality.’ We included children with the ability to walk, their parents, and their PPTs. The training was evaluated by analyzing PPTs’ knowledge, skills, and confidence using the AM-p Toolkit. Quantitative results were analyzed descriptively (mean [SD] and median [interquartile range] when appropriate and qualitative data were analyzed thematically. Results Fifteen PPTs, 17 parents, and 20 children completed the study. PPTs rated overall satisfaction on a 10-point scale with the AM-p Toolkit at 6.3 (SD 1.2), and parents rated it 7.3 (SD 1.6). The following themes emerged for acceptability, demand, and practicality respectively: for acceptability: 1) expected added value, 2) quality and usability, and 3) design; for demand: 1) use and non-use, 2) further development, and 3) willingness for future use; and for practicality: 1) time constraints and 2) integration. Conclusion The AM-p Toolkit shows promise in PPT, with generally positive acceptability among all end-users. PPTs see potential for certain groups of children who can benefit from the AM-p Toolkit. Practicality requires improvements in the web application and refinement of the strap. Training is important and can be strengthened by emphasizing the analysis of assessment results, clinical reasoning, and functional goal-setting.